2017
DOI: 10.18535/ijmsci/v4i3.05
|View full text |Cite
|
Sign up to set email alerts
|

A study on Factors associated with non-adherence to ATT among pulmonary tuberculosis patients under RNTCP

Abstract: INTRODUCTION-India is the second-most populous country in the world but unfortunately, one fourth of the global incident TB cases occur in India annually. Tuberculosis treatment need multi drug combination to eradicate tuberculosis bacteria. Inability to complete the prescribed regimen, is an important cause of treatment failure, relapse, acquired drug resistance and continuous transmission of infection. OBJECTIVES-1. To study the sociodemographic characteristics of pulmonary tuberculosis patients under RNTCP.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…25 Study by Aashutosh Asati et al, has also shown that TB was found to be significantly associated with male gender, married individuals, smoking, drinking, and illiteracy. 26 Number of patients with a known history of contact with tubercular patient was higher in group 'A' patients i.e. 15% as compared to 6.8 % in group B in younger aged patients without any much difference among elders.…”
Section: Associated Risk Factors/habitsmentioning
confidence: 75%
“…25 Study by Aashutosh Asati et al, has also shown that TB was found to be significantly associated with male gender, married individuals, smoking, drinking, and illiteracy. 26 Number of patients with a known history of contact with tubercular patient was higher in group 'A' patients i.e. 15% as compared to 6.8 % in group B in younger aged patients without any much difference among elders.…”
Section: Associated Risk Factors/habitsmentioning
confidence: 75%
“…In our study, factors significantly associated with this group were patient's age, educational status, wealth index and type of health services from where treatment was sought for other illnesses. Other studies too have reported age, illiteracy, and poor socioeconomic status as risk factors for default . There is a need to focus on this high‐risk group with enhanced counselling and follow‐up services to retain them in the treatment network.…”
Section: Discussionmentioning
confidence: 99%